Characteristics, Properties and Analytical/Bioanalytical Methods of 5-Aminosalicylic Acid: A Review - Tavares Junior, Alberto Gomes [UNESP]; de Araújo, Jennifer Thayanne Cavalcante [UNESP]; Meneguin, Andréia Bagliotti [UNESP]; Chorilli, Marlus [UNESP] (Taylor & Francis, 2020)
Five-aminosalicylic acid (5-ASA) is an anti-inflammatory drug indicated in the treatment of inflammatory bowel diseases such as ulcerative colitis and Crohn's disease. Among the analytical methods of quantification of 5-ASA described in the literature, the High Efficiency Liquid Chromatography stands out, a sensitive technique but with a high cost. In recent years, alternative methods have been developed, presenting efficiency and reduced cost, such as UV/visible spectrophotometric, spectrofluorescent, and electrochemical methods, techniques recommended for the application in quality control and quantification of 5-ASA in pharmaceutical forms and biological fluids. This article aims to review the physicochemical characteristics, pharmacokinetics, mechanisms of action, controlled release systems, and the different analytical and bioanalytical methods for the quantification of 5-ASA.
Keywords: 5-ASA; Analytical methods; drug delivery systems; mechanisms of action; physicochemical characteristics